Tindak Pidana Prostitusi dalam Tinjauan KUHP dan Hukum Pidana Islam di Desa Kesilir Wuluhan Jember - Senja Fita Sari; Abdul Wahab (Sharia Faculty, Kiai Haji Achmad Siddiq State Islamic University of Jember, 2021)
This research is motivated by the criminal activity of the crime of prostitution which is a disgraceful activity and an activity that is very contrary to religious, social and legal norms. Therefore, these activities must be destroyed by implementing the legal rules that have been made and providing direction and guidance in order to understand all forms of behavior that can violate religious, social and legal norms. From this background, the writer takes the focus of the research; 1) what are the factors that cause the emergence of criminal acts of prostitution in Kesilir Village?, 2) How is the implementation of Article 296 of the Criminal Code in conjunction with 506 of the Criminal Code against the crime of prostitution in Kesilir Village?, 3) How is the review of Islamic Criminal Law in processing crime crimes? prostitution crime? This study uses a qualitative approach with the type of case study research conducted in the village of Kesilir Wuluhan Jember. Determination of research subjects using purposive techniques with primary data sources and secondary data. Data collection techniques used non-participant observation, unstructured interviews and documentation as well as interactive data analysis.